Heparin-induced thrombocytopenia: new insights into the immune response - Cosmi, Benilde (Translational Cancer Research, 2017)
Heparin induced thrombocytopenia (HIT) is an immuno mediated adverse reaction to heparin (both unfractionated and low molecular weight) due to the development of IgG antibodies against a self antigen, that is the complex of platelet factor 4 (PF4) and heparin or other polyanions. The IgG/heparin-PF4 immunocomplexes can cross-link with the Fcγ receptor IIa (FcγRIIa) on platelet surface. As a consequence, platelets are activated with intravascular aggregation and consumption, leading to thrombocytopenia. However, a paradoxical prothrombotic state ensues with coagulation activation and life-threatening venous and/or arterial thrombotic complications (1).